Professional Zakat: A Contemporary Fiqh Solution in the Era of Modern Income - Mutia Chairunnisa; Khadijah Khadijah; Widya Sari (Lembaga Penerbitan dan Publikasi Ilmiah Yayasan Pendidikan Tumpuan Bangsa, 2025)
This study explores the issue of unfamiliarity with professional zakat among Indonesian Muslims, where types of professional income such as doctors' or lawyers' salaries have not been fully recognized as objects of zakat, even though they have great potential to support social welfare. The main purpose is to examine the legal basis of professional zakat through analogy (qiyas) with other property zakat, as well as to formulate provisions and calculation methods in accordance with the modern economic context, in order to improve understanding and application in society. The method used is a qualitative approach with library research, involving content analysis of classical and contemporary literature sources such as the fiqh book of Yusuf al-Qardhawi, scholarly interpretation, and modern studies of professional zakat. The results of the study show that professional zakat has a strong shari'i basis from Qur'anic verses and general hadiths, with qiyas on trade zakat as the most moderate approach (nisab 85 grams of gold, 2.5% level, one-year haul), as well as the flexibility of calculation between gross or net income based on muzakki conditions. Recommendations include intensive education by zakat institutions and the development of a practical calculation model to introduce professional zakat as an integral part of Islamic social worship.